Nanostructured surface enhanced boiling for advanced cooling - Ho, Jin Yao (2015)
With continuous increase in transistor packing density along with component miniaturisation, highly efficient cooling schemes are required to better cope with the exponential rise in chip level heat flux. In this aspect, nucleate pool boiling with the coating of carbon nanotube (CNT) onto heat transfer surfaces using chemical vapour deposition (CVD) technique has been shown to be an effective cooling method which could be applied in various cooling schemes. However, the thermal transport mechanisms from these surfaces and their nucleation boiling heat transfer characteristics under different parameters such as coating areas and surface orientation are still not well understood. In this thesis, detailed investigations on saturated pool boiling heat transfer of CNT coated surfaces with FC-72 as the coolant fluid are presented. In total, two batches of CNT coated surfaces of different silicon substrate surface roughness and CNT coating configuration were produced. In the first batch, 30%, 60%, 90% and interlaced 60%-CNT surfaces were coated on bare silicon of 450 nm surface roughness whereas in the second batch, 100% and interlaced 70%-CNT surfaces were fabricated on bare silicon of 15 nm surface roughness. In addition to saturated pool boiling conducted at 0° (upright) surface orientation, a range of surface orientations from 0° to 180° for the second batch of CNT surfaces were also investigated. The investigations revealed that CNT coating resulted in lower heat fluxes and lower wall superheats for boiling incipience as compared to the base substrate (bare silicon). In addition, critical heat flux (CHF) and nucleate boiling heat transfer were also enhanced by the CNT coating where the magnitude of enhancement were found to increase with increasing CNT coating area and perimeter. On the other hand, increasing surface orientations exhibited adverse effect on the heat transfer performance of CNT coated surfaces where substantial reduction in the average heat transfer coefficient with surface orientations of 60° and above were observed. By performing high speed imaging, surface microstructure and surface wettability analyses, mechanisms for boiling incipience, nucleate boiling, CHF and the effect of surface orientations of the CNT coated surfaces on boiling heat transfer performance are elucidated. With the experimental data obtained, correlations are proposed for the average heat transfer coefficient (have) and CHF for the second batch of CNT surfaces with the effect of surface orientations. Finally, based on the Rohsenow model [24] for nucleate pool boiling, a general correlation for characterising the saturated pool boiling curves of CNT coated surfaces, including the effects of CNT coating area and perimeter, substrate surface roughness and surface orientations, was developed. The correlation shows good agreement with the experimental results.